Algoritmo de Optimización para el despacho económico de una micro red distribuida. - Amores Moreno, Ana Gabriela (2022)
This research work establishes the application of an optimization algorithm for distributed generation considering initially photovoltaic panels (PV), batteries (BESS), wind generator (WT) and thermal generator (DGS), it allows optimal planning both in the implementation and in the dispatch of energy considering that the maximum cost of implementation is $6,000, costs for emission of CO2 and fuel, the programming was carried out through the FICO XPRES software, the case study is the load of a Hostería in Mulaló sector. Measures acquired within a year of renewable resources are taken into consideration. Two equations are considered: The first consists of an equation based on the sum of maximum powers, the results obtained show that the most critical month is in August since the (DGS) contributes with 382.56 KWh per month, that is, 48% of the supplied energy generating 177.14 Kg of CO2. The second equation consists of applying a mixed integer algorithm that plans a contribution of (DGS) of 63KWh per month, generating 27.7 Kg of CO2, with a reduction of 83%. In the month of February, the optimizer plans the exclusive resource of renewable energy, the penalty costs for gas emission and fuel use drop from $5.81 to $0.34 per day, in the two simulation cases it does not consider PV generation